2013
DOI: 10.1111/insr.12029
|View full text |Cite
|
Sign up to set email alerts
|

Varying Coefficient Regression Models: A Review and New Developments

Abstract: SummaryVarying coefficient regression models are known to be very useful tools for analysing the relation between a response and a group of covariates. Their structure and interpretability are similar to those for the traditional linear regression model, but they are more flexible because of the infinite dimensionality of the corresponding parameter spaces. The aims of this paper are to give an overview on the existing methodological and theoretical developments for varying coefficient models and to discuss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 82 publications
0
53
0
Order By: Relevance
“…Another is to set each regression coefficient be function of different variables. There are various extensions of VCM ( Park et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another is to set each regression coefficient be function of different variables. There are various extensions of VCM ( Park et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This model is gaining its popularity in statistics literature in recent years. The introductions, various applications and current research areas of the varying coefficient model can be found in [4,5,3,11]. Many areas of applied statistics have become aware of the problem of estimating varying coefficients and analyzing them appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…There are various extensions of models. See [11] for details. Most literature has centered around the case that all regression coefficients are functions of a single vector of covariates.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known time-varying-coefficient models for longitudinal data should be mentioned as well. For a recent review see Park et al (2015). The extension of (4) to (3) is just an extension of the classical nonparametric varying-coefficient model toward a non-or semiparametric mixed effects model, see for example González Manteiga et al (2013).…”
Section: Introductionmentioning
confidence: 99%